Harmonization of Islamic Law and Local Wisdom: A Methodological Reconstruction of Ijtihad in Family Law Based on Yusuf al-Qaradawi’s Istinbāṭ Approach - Imam Syafi'i; Ramdan Wagianto; Hawa’ Hidayatul Hikmiyah; Irzak Yuliardy Nugroho; Syaikhoni (Islamic Research Publiser, 2026)
This article examines the harmonization of Islamic law and local wisdom in family law issues through the development of the ijtihad method from the perspective of Yusuf al-Qaradawi's istinbāṭ method. Given that contemporary Muslim family issues are increasingly complex, this study emphasizes the need for an istinbāṭ framework that maintains the authenticity of naṣṣ while being responsive to social realities. This study employs a qualitative-normative approach, using usul al-fiqh analysis, and examines al-Qaradawi's key concepts as instruments for integrating local wisdom. Data were collected from exploring library materials related to Yusuf al-Qaradawi's works within the framework of istinbāṭ that was developed. The results of this study show that Yusuf al-Qaradawi developed an istinbāṭ method called istinbāṭ at-taysīr with three types, namely intiqā’iy tarjīhiy, ibdā’iy insyāiy, and intiqā’iy insyā’iy. This method combines as-salafiy, which does not adhere to the opinions of the fiqh schools, and al-mażhabiy, which is guided by the opinions of the imams of the schools, by re-examining the various opinions of the scholars or conducting their own ijtihad and choosing the opinion that provides leniency, provides convenience, is in accordance with the conditions, and combines local wisdom, to realize the greater good. The contribution of this article lies in providing a methodological model to bridge the tension between textuality and contextuality in family law, while offering academics and policymakers a basis for formulating norms that are more just, relevant, and in line with the demands of modern society.